Plastic pollutions in the ocean: their sources, causes, effects and control measures - Aminur Rahman, M.; Mojumdar, Shoumik; Asif Rahman, Sk.; Marimuthu, Kasi (Journal of Biological Studies, 2023)
Plastic pollution in the ocean is a global concern; concentrations reach 580,000 pieces/km2 and production is increasing exponentially. Plastic pollution is a widespread problem affecting the marine environment. It threatens ocean health, the healthiness of marine species, food safety and quality, human health, coastal tourism, and contributes to climate change. Given the persistent nature of plastic and its toxicity, pollution caused by plastic is a significant threat to biodiversity. It threatens ecosystems, animal and plant species, impeding their ability to deliver essential services to humanity. The most visible impacts of plastic debris are the ingestion, suffocation and entanglement of hundreds of marine species. Marine wildlife such as seabirds, whales, fish and turtles mistake plastic waste for prey; most then die of starvation as their stomachs become filled with plastic. They also suffer from lacerations, infections, reduced ability to swim, and internal injuries. Floating plastics also help transport invasive marine species, thereby threatening marine biodiversity and the food web. Microplastics have been found in tap water, beer, salt and are present in all samples collected in the world’s oceans. Several chemicals used in the production of plastic materials are known to be carcinogenic and to interfere with the body’s endocrine system, causing developmental, reproductive, neurological, and immune disorders in both humans and wildlife. Recently, microplastics are found in human placentas but more research is needed to determine if this is a widespread problem. Toxic contaminants also accumulate on the surface of plastic as a result of prolonged exposure to seawater. When marine organisms ingest plastic debris, these contaminants enter into their digestive systems, and over time accumulate in the food web. The transfer of contaminants between marine species and humans through consumption of seafood has been identified as a health hazard, and research regarding the matter is going on. Plastic waste damages the aesthetic value of tourist destinations, leading to decreased income from this sector. It also generates major economic costs related to the cleaning and maintenance of the sites. The build-up of plastic litter on beaches can have a negative impact on a country’s economy, wildlife, and the physical and psychological wellbeing of people. Plastic production contributes to climate change. For example, if plastic waste is incinerated, it releases carbon dioxide and methane (from landfills) into the atmosphere, thereby increasing emissions. Plastic has invaded every corner of the Earth, from glaciers in the Arctic to the sands of the Sahara. It is not surprising to find plastic bottles, snack packages, abandoned fishing gear and many other pieces of waste floating alongside beautiful corals and schools of fish. But one can help prevent an even more plastic-filled future for our oceans. Here are 5 tips to get one started such as (a) Do not buy it in the first place (but if you do, reuse it); (b) Do a mental checklist every time of shopping; (c) Shop for food locally and sustainably; (d) Shrink the carbon footprint; (e) Clean up; and (f) A roadmap for using nature as a climate solution.